KORELASI ANTARA MINAT, MOTIVASI DENGAN HASIL BELAJAR TEMATIK SISWA KELAS IV SEKOLAH DASAR NEGERI - Hariani, Hariani; Kartono, Kartono; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimd to describe the correlation between learning interest, learning motivation, and learning outcomes in the thematic learning of Grade IV 14 Primary Schools in South Pontianak. The method used is descriptive method in the form of research studies of relationships (Interrelationship Studies) by using correlation studies. This study is a population study with a total of 28 students. Data collection techniques in this research are indirect communication techniques and documentary study techniques. Data collection tools used were questionnaires and learning outcomes documents. The results showed that students' interest in learning at 14 South Pontianak Elementary School was classified as 88.94% with an average of 111.18 and student learning motivation at 88.90% with an average of 88.90. While the learning outcomes of 14 Pontianak South Elementary School students obtained an average of 81.60. Based on the results of statistical calculations using the product moment correlation formula for the calculation of students' learning interest the r count result is 0.285. As for the calculation of students' learning motivation, the r count result is 0.266. For the calculation of interest in learning, learning motivation with student learning outcomes obtained r count of 0.431, while the r table of 0.367 means r count > r table or (0.431> 0.367). Based on the results of the study, the relationship between interest in learning, motivation to learn with student learning outcomes in thematic learning class IV Elementary School 14 South Pontianak in the medium category.        Keywords: Interest in Learning, Learning Motivation, Learning Outcomes,                             Thematic.